Understanding sexual and reproductive health from the perspective of late adolescents in Northern Thailand: a phenomenological study - Panitsara Leekuan; Ros Kane; Panpimol Sukwong; Waratya Kulnitichai (BMC, 2022)
Abstract Background Worldwide, Sexual Reproductive Health (SRH) issues comprise a third of health problems for women aged 15-44. SRH education equips people with knowledge of concepts around sexuality and reproduction, and the skills help to make informed decisions to prevent sexual and reproductive ill-health, including unplanned pregnancy and HIV/AIDS, and other sexually transmitted infections (STIs). The aim of this study was to explore the experiences of late adolescents relating to SRH, examining their attitudes toward sex and contraception, and to identify the gaps in knowledge pertiaing to decision-making around risk-taking behaviour. Methods A qualitative phenomenological study was undertaken with 30 adolescents aged 18-19, purposively and snowball sampled from a university in Northern Thailand. Data collaction took place from July 2020 to January 2021. In-depth individual interviews were conducted until data saturation was reached. Data were recorded, transcribed, and analysed in ATLAS.ti version 9, using Modified Interpretative Phenomenological Analysis to identify pertinent themes. Results Participants revealed five key experiences of SRH related to sex and contraception: Keeping a secret; Seeking Freedom and Love; Having SRH education; Self-protection; Parental acceptance. All findings reflected the value and impact of SRH on the experiences of late adolescents. Conclusions This study provides detailed knowledge about adolescents' perspectives of SRH and rights in terms of accessing sexual and reproductive health care and information as well as autonomy in sexual and reproductive decision-making. Gaining SRH education can assist decision-making concerning contraceptive methods for family planning and STI prevention. The study recommends that SRH and rights-based education should be designed responsively and appropriately for female and male adolescents, their families, and society. The content of SRH should be informed and advocated by healthcare providers, educators, policy makers, and systems to empower adolescents in order to achieve effective SRH education.